Assessment of genetic variability, heritability and genetic advance for yield and yield contributing traits in Mesta (Hibiscus spp.): Assessment of genetic variability, heritability and genetic advance for yield and yield contributing traits in Mesta (Hibiscus spp.) - D RAGHU VARMA; A M MISAL; P L TAVADARE (Journal of Oilseeds Research, 2020)
The present investigation was conducted to estimate the extent of genetic variability, heritability and genetic advance in Mesta (Hibiscus spp. L). A set of 110 genotypes were evaluated at Oilseeds Research Station, Latur during kharif, 2018. Substantial amount of genetic variability was observed for all the characters studied. The estimates of genotypic coefficient of variances (GCV) and phenotypic coefficient of variances (PCV) were high for some characters. High heritability estimates were observed for all the traits under the study. However, high genetic advance as per cent of mean was noted for all the characters except for days to maturity where it was moderate. Much variability was present in the material for all the characters which can be used in the future by simple selection.